تقييم تجارب التشديد ودراسة البارامترات المؤثرة على عامل التشوه الأدومتري - الزاوي, منذر; طريفة, حسان (Latakia University Journal -Engineering Sciences Series, 2018)
Mixed soils have the properties of the components in their composition, so the odometer modulus and other consolidation parameters will be clearly affected when the soil is transformed from pure into mixed. So, we conducted the necessary tests on the soil of net clay which added to it varying percentages of pure sand to monitor the behavior of mixed clay soils by proportion of sand in the composition ,and the odometer tests were examined and the properties of the consolidation parameters were studied in relation to the Eoed odometer modulus as such comparisons were also made between undisturbed samples and disturbed samples which remoulding in experiments. The results showed some differentiation of the characteristics of the undisturbed samples from the disturbed samples because they are pre-stressed ,as the results showed an increase in the odometer modulus Eoed when increasing the sand ratio in the sample and a clear decrease in the values of the consolidation parameters such as (Cc, Cr, Cs , E, Mv) when mixing ratio exceeds 20%, which is consistent with research conducted in this field. إن الترب المختلطة لديها خصائص المكونات التي تدخل في تركيبها, وبالتالي فإن عامل التشوه الأدومتري وبارامترات التشديد الأخرى سوف تتأثر بشكل واضح عندما تتحول التربة من صافية إلى مختلطة. لذلك قمنا بإجراء الاختبارات اللازمة على ترب ناعمة صافية أضيفت إليها نسب متفاوتة من الرمل الصافي بهدف رصد سلوكية الترب المختلطة, وذلك فيما يتعلق - على وجه الخصوص - بمعامل التشوه الأدومتريEoed , وقد أجريت تجارب الأدومتر ودرست خصائص بارامترات التشديد في علاقتها مع عامل التشوه الأدومتري Eoed كما أجريت مقارنات ما بين العينات السليمة والعينات المخربة المشكلة مخبرياً. وبينت النتائج بعض التمايز لخواص العينات السليمة عن العينات المخربة بسبب كونها مسبقة التشديد, كما بينت النتائج تزايداً في معامل التشوه الأدومتري Eoed عند زيادة نسبة الرمل في العينة, وتناقصاً واضحاً كذلك في قيم بارامترات التشديد مثل (Cc , Cr , Cs , e , Mv) عندما تزيد نسبة الخلط عن 20% وهذا ما يتوافق مع الأبحاث المجراة في هذا المجال.